The current use of patient-centered/reported outcomes in implant dentistry: a systematic review - De Bruyn, Hugo; Raes, Stefanie; Matthys, Carine; Cosyn, Jan (Clinical oral implants research, 2015)
Aim To provide an update on the use of Patient‐Reported Outcome Measures (PROMs) in the field of implant dentistry (1); to compare PROMs for prostheses supported by one or more implants to alternative treatment options or a healthy dentition (2). Materials and methods The dental literature was searched on PubMed until December 31, 2014, using a general search algorithm. An overall quantitative analysis was performed, and a qualitative appraisal was made on the output of the last 6 years. Per type of edentulism and prosthetic treatment, the general search algorithm was refined in order to select controlled studies comparing PROMs for prostheses supported by one or more implants to alternative treatment options or a healthy dentition. Results With nearly half of the output (300 of 635) published in the last 6 years, there is a growing interest in PROMs by the scientific community. When scrutinizing the 300 most recent publications, only 84 controlled studies could be identified among which 38 RCTs and 31 cohort studies. An “ad hoc” approach is commonly employed using non‐standardized questions and different scoring methods, which may compromise validity and reliability. Overall, 39 eligible papers related to fully edentulous patients treated with an implant overdenture (IOD) and 9 to fully edentulous patients treated with a fixed implant prosthesis (FIP). There is plenty of evidence from well‐controlled studies showing that fully edentulous patients in the mandible experience higher satisfaction with an IOD when compared to a conventional denture (CD). This may not hold true for fully edentulous patients in the maxilla. In general, fully edentulous patients seem to opt for a fixed or removable rehabilitation on implants for specific reasons. Data pertaining to partially edentulous patients were limited (FIP: n = 6; single implants: n = 16). In these patients, the timing of implant placement does not seem to affect patient satisfaction. Patients seem to prefer straightforward implant surgery over complex surgery that includes bone grafting. Conclusion There is an urgent need for standardized reporting of PROMs in the field of implant dentistry. Fully edentulous patients in the mandible experience higher satisfaction with an IOD when compared to a CD. All other types of prostheses have been underexposed to research.